Amniotic-fluid Lactoferrin: A Marker for Subclinical Intraamniotic Infection Prior to 32 Weeks Gestation. Issue 5 (1995) - Heller, Kimberly A.; Greig, Phillip C.; Heine, R. Phillip
Abstract : Objective: Lactoferrin is a glycoprotein released from the secondary granules of activated neutrophils in the setting of infection. The purpose of this study was to determine if amniotic-fluid (AF) lactoferrin levels are elevated in preterm labor (PTL) patients with subclinical intraamniotic infection (IAI). Methods: AF samples were obtained from 186 pregnant patients with the following characteristics: group 1 - term, no labor; group 2 - preterm, no labor; group 3 - PTL with IAI; group 4 - PTL without IAI. Lactoferrin levels were measured with an enzyme-linked immunosorbent assay (ELISA). Results: AF lactoferrin levels were elevated in normal gestation after 31 weeks (P < 0.0001). Lactoferrin levels were also higher in infected PTL patients compared with noninfected PTL patients at gestations ≤31 weeks (P = 0.005). An AF lactoferrin level of >2.5 μg/ml is highly suggestive of infection in PTL patients at <32 weeks, with an overall sensitivity of 82% and a specificity of 83%, when infection is defined as a positive AF culture or positive placental histology. Conclusions: AF lactoferrin levels increase after 31 weeks in normal gestations, but lactoferrin levels >2.5 μg/ml in PTL patients before this gestational age are highly suggestive of IAI. AF lactoferrin levels may be a useful clinical tool for selecting those PTL patients who might benefit from antimicrobial therapy, closer observation, or early delivery.